Knowledge, Attitude and Practices Regarding Professional Indemnity Insurance among Dental Professionals in Teaching Institutes of Peshawar - Hameed , Amir; Ahad , Babar; Khan, Zohaib; Aleem, Saima (Journal of Liaquat University of Medical & Health Sciences, 2026)
OBJECTIVE: To evaluate dental professionals' knowledge, attitudes, and practices regarding dental indemnity insurance (PII) at teaching institutions in Peshawar. METHODOLOGY: A cross-sectional study was conducted from July 2019 to March 2020 among 276 dentists holding a Bachelor's in Dentistry degree and practising in either government or private teaching institutions in Peshawar. Initially, proportionate sampling was used to allocate samples required across the seven study sites, and a random sampling technique was used to recruit samples from the sites. Data were collected using a validated questionnaire covering socio-demographic characteristics, awareness of PII, and perceptions regarding compensation for dental negligence, and were analyzed using SPSS version 23.0. Ethical approval was obtained, and written informed consent was secured from all participants. RESULTS: Out of 274 respondents (99.8% response rate), 93.8% lacked knowledge of PII, and only 6.2% had insurance coverage. While 64.2% believed PII should be mandatory, 73% were unaware of its existence. Gender, age, and experience did not significantly influence awareness. The majority of participants (77%) had never been asked for compensation, but opinions on compensation amounts for negligence varied widely. CONCLUSION: The study highlights a significant knowledge gap and low uptake of PII among dental professionals in Peshawar. Addressing barriers such as awareness, affordability, and regulatory enforcement is essential to ensure financial protection for practitioners and enhance patient trust.